2014
DOI: 10.1037/a0037116
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation and gender within a game-based learning environment.

Abstract: In this study, we examined how self-regulated learning (SRL) and gender influences performance in an educational game for 8th-grade students (N ϭ 130). Crystal Island-Outbreak is an immersive, inquirybased, narrative-centered learning environment featuring a microbiology science mystery aligned with 8th-grade science curriculum. SRL variables predicted successful in-game performance even after accounting for prior knowledge and perceived gaming skill. Content learning gains were found across both genders, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 74 publications
1
39
1
2
Order By: Relevance
“…Gender differences in computer game self-efficacy likely result from differences in exposure to and experience with computer games as well as the gendered cultural messages boys and girls receive about computer game playing (Bussey and Bandura 1999;Terlecki et al 2011). Despite gender differences in mean computer game self-efficacy, results from the multi-group modeling suggested only minor differences between boys and girls in the relations among efficacy beliefs and module performance, consistent with recent work by Nietfeld et al 2014. The absence of significant gender differences in how self-efficacy beliefs relate to IVE performance is important as it suggests that the SAVE Science assessment is equitable with regard to gender, even while gender differences in computer game self-efficacy are observed.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Gender differences in computer game self-efficacy likely result from differences in exposure to and experience with computer games as well as the gendered cultural messages boys and girls receive about computer game playing (Bussey and Bandura 1999;Terlecki et al 2011). Despite gender differences in mean computer game self-efficacy, results from the multi-group modeling suggested only minor differences between boys and girls in the relations among efficacy beliefs and module performance, consistent with recent work by Nietfeld et al 2014. The absence of significant gender differences in how self-efficacy beliefs relate to IVE performance is important as it suggests that the SAVE Science assessment is equitable with regard to gender, even while gender differences in computer game self-efficacy are observed.…”
Section: Discussionsupporting
confidence: 85%
“…Despite ongoing changes in the type and availability of video and computer games, researchers consistently find that males report liking and playing video games more than females (e.g., Buchman and Funk 1996;Hartmann and Klimmt 2006;Lucas and Sherry 2004;Nietfeld et al 2014;Terlecki et al 2011;Turkle 1995;Wright et al 2001). As with science self-efficacy, gender differences in computer game self-efficacy may stem from a variety of social influences-home, education, cultural, mass media-that shape the experiences and perceptions that adolescents have with regard to gaming as a male stereotyped activity (Terlecki et al).…”
Section: Gender Differencesmentioning
confidence: 97%
“…The pretest and posttest assessment sequence of items were randomized from pretest to posttest administration to reduce practice effects. Both the pretest and posttest are validated instruments that were adopted from Nietfeld, Shores, and Hoffmann (2014). Questionnaires not included in our analyses were not included due to space limitations.…”
Section: Methodsmentioning
confidence: 99%
“…Gender is a common line of investigation in technology‐related research, with known differences for engagement style and frequency and duration of use of digital media among boys and girls (McFarlane, et al ., 2000; McFarlane, Sparrowhawk, & Heald 2002). Gender differences are more pronounced and are typically studied for older age groups in relation to digital games (eg, Nietfeld, Shores, & Hoffman, ) and social media engagement (eg, Suchert, Hanewinkel, Isensee, & Läuft Study Group, ). However, a national survey carried out by Ofcom in 2014 in the UK showed that there are some gender differences in media use even at a very young age: 30% of boys aged 3–4 years use a handheld/portable games player, compared to 21% girls aged 3–4 years.…”
Section: Children's Gendermentioning
confidence: 99%